Biological data from sharks landed within the United Arab Emirates artisanal fishery. Issue 2 (19th August 2016) - Jabado, RW; Al Ghais, SM; Hamza, W; Robinson, DP; Henderson, AC
Abstract : Landing site and market surveys of sharks landed along the Arabian Gulf coast of the United Arab Emirates were undertaken between October 2010 and September 2012 to obtain biological data from this artisanal fishery. Data were collected on the size and sex of 12 482 individuals representing 30 species. Maximum sizes of Carcharhinus sorrah, C. amblyrhynchoides and Hemipristis elongata were extended by at least 300 mm total length (TL) compared with published global maxima. The size at 50% maturity was determined for males of five species and this indicated that the males of smaller shark species (<1 000 mm maximum TL) in the fishery were largely mature. For many species, including Loxodon macrorhinus and Mustelus mosis, overall sex ratios were male-biased, indicating that sexual segregation is likely in those species. Furthermore, sex ratios for several species, such as Rhizoprionodon acutus, showed differences across seasons. Overall, the landings contained a high proportion of juveniles, causing concerns about the sustainability of this fishery. Biological parameters of a number of species differed from those recorded earlier for the region, demonstrating a need for additional local data collection to support the development of management measures.